Causes of Severe Visual Impairment and Blindness: Comparative Data From Bhutanese and Laotian Schools for the Blind. Issue 6 (November 2015) - Farmer, Lachlan David Mailey; Ng, Soo Khai; Rudkin, Adam; Craig, Jamie; Wangmo, Dechen; Tsang, Hughie; Southisombath, Khamphoua; Griffiths, Andrew; Muecke, James
Abstract : Purpose: To determine and compare the major causes of childhood blindness and severe visual impairment in Bhutan and Laos. Design: Independent cross-sectional surveys. Methods: This survey consists of 2 cross-sectional observational studies. The Bhutanese component was undertaken at the National Institute for Vision Impairment, the only dedicated school for the blind in Bhutan. The Laotian study was conducted at the National Ophthalmology Centre and Vientiane School for the Blind. Children younger than age 16 were invited to participate. A detailed history and examination were performed consistent with the World Health Organization Prevention of Blindness Eye Examination Record. Results: Of the 53 children examined in both studies, 30 were from Bhutan and 23 were from Laos. Forty percent of Bhutanese and 87.1% of Laotian children assessed were blind, with 26.7% and 4.3%, respectively, being severely visually impaired. Congenital causes of blindness were the most common, representing 45% and 43.5% of the Bhutanese and Laotian children, respectively. Anatomically, the primary site of blinding pathology differed between the cohorts. In Bhutan, the lens comprised 25%, with whole globe at 20% and retina at 15%, but in Laos, whole globe and cornea equally contributed at 30.4%, followed by retina at 17.4%. There was an observable difference in the rates of blindness/severe visual impairment due to measles, with no cases observed in the Bhutanese children but 20.7% of the total pathologies in the Laotian children attributable to congenital measles infection. Conclusions: Consistent with other studies, there is a high rate of blinding disease, which may be prevented, treated, or ameliorated.